Routine laboratory biomarkers as prognostic indicators of cardiac sarcoidosis outcomes - Kolluri, Nikhil; Schmidt, Tyler; Elwazir, Mohamed; Kapa, Suraj; AbouEzzeddine, Omar; Bois, John; Schirger, John; Rosenbaum, Andrew; Cooper, Leslie (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Biomarkers to monitor disease activity and predict major adverse cardiac events (MACE) in CS have not been described previously. We aimed to identify biomarkers to predict MACE in cardiac sarcoidosis (CS).Methods: Patients (N=232) diagnosed with CS were retrospectively enrolled. Biomarkers including angiotensin-converting enzyme (ACE), N-terminal brain natriuretic peptide (NT-proBNP), troponin T, and creatinine levels were evaluated against a primary end point of left ventricular assist device implantation, heart transplantation, or death, and a secondary end point of cardiac hospitalization-free survival.Results: Troponin T (hazard ratio [HR], 1.06 per 0.01 ng/mL; P=.006), NT-proBNP (HR, 1.31 per 1,000 pg/mL; P